Fibronectin synthesis in tubular epithelial cells: up-regulation of the EDA splice variant by transforming growth factor β - Viedt-Suelmann, Christiane; Bürger, Antje; Hänsch, Gertrud Maria (Kidney international, 1995)
Fibronectin synthesis in tubular epithelial cells: Up-regulation of the EDA splice variant by transforming growth factor β. The influence of transforming growth factor β1 (TGF-β1) and of dexamethasone on fibronectin (FN) synthesis of human renal tubular epithelial cells in culture (TEC) was studied. Cocultivation with TGF-β1 increased the steady state level of FN RNA within 24 to 48 hours. By PCR and Northern blotting it was found that the EDA splice variant of FN was preferentially up-regulated. To quantitate FN protein synthesis, cells were cultivated in the presence of [35S]-methionine and FN was isolated from the cell supernatants, and the cell lysates by adsorption to gelatin-sepharose. In TGF-β1 treated cells, a small increase of FN in the cell supernatants was seen (1.7-fold), and a more prominent increase in the cell lysates (4.5-fold). The FN content of the extracellular matrix was also increased in TGF-β1 treated cells. Most of the de novo synthesized FN was identified as the EDA-variant of FN. As a further stimulus, dexamethasone was used. Again, an increase of FN-specific mRNA was seen as well as an increased FN protein synthesis. The ratio between FN and EDA-FN, however, was not altered when compared to untreated cells. Thus, an increase in EDA-FN synthesis is obviously stimulus dependent.